2015
DOI: 10.1128/mcb.01133-14
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Ran System by Cysteine Oxidation of the Nucleotide Exchange Factor RCC1

Abstract: Transport regulation by the Ran GTPase requires its nuclear localization and GTP loading by the chromatin-associated exchange factor RCC1. These reactions generate Ran protein and Ran nucleotide gradients between the nucleus and the cytoplasm. Cellular stress disrupts the Ran gradients, but the specific mechanisms underlying this disruption have not been elucidated. We used biochemical approaches to determine how oxidative stress disrupts the Ran system. RCC1 exchange activity was reduced by diamide-induced ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…3C). In human, cellular stress and elevated H 2 O 2 levels disrupt the Ran system, and this was partly attributed to cysteine oxidation of the nucleotide exchange factor RCC1, although independent mechanisms were suggested (48). Cys-SOH in the active sites of AtLSF2 and AtSEX4 (SI Appendix, Table S2) align with the nucleophilic Cys of 2 human Protein Tyr Phosphatases (PTPs), VACCINIA H1-RELATED PHOSPHATASE (HsVHR) and SLINGSHOT HOMOLOG3 (HsSSH3) (Fig.…”
Section: S-sulfenylation At Specific Cysteine Sites Affects Protein Fmentioning
confidence: 99%
“…3C). In human, cellular stress and elevated H 2 O 2 levels disrupt the Ran system, and this was partly attributed to cysteine oxidation of the nucleotide exchange factor RCC1, although independent mechanisms were suggested (48). Cys-SOH in the active sites of AtLSF2 and AtSEX4 (SI Appendix, Table S2) align with the nucleophilic Cys of 2 human Protein Tyr Phosphatases (PTPs), VACCINIA H1-RELATED PHOSPHATASE (HsVHR) and SLINGSHOT HOMOLOG3 (HsSSH3) (Fig.…”
Section: S-sulfenylation At Specific Cysteine Sites Affects Protein Fmentioning
confidence: 99%
“…Postmitotic cells are unable to repair damaged nuclear pores, which become leaky during aging. Oxidative stress, a well-known hallmark of aging and implicated in several neurodegenerative disorders [ 65 ], is known to cause such damage to the nuclear pore [ 23 , 140 ], but also to other components of the nuclear transport machinery [ 18 , 59 ]. Several nuclear transport factors themselves have already been found misregulated in post - mortem ALS and FTLD patient material [ 58 , 84 , 92 , 126 , 144 ] (Fig.…”
Section: Nuclear Transport Defects Are Implicated In Als and Ftldmentioning
confidence: 99%
“…However, disulfide bonding of the condensin subunit CAP-G (Kuga et al, 2007), RCC1 (Chatterjee and Paschal, 2015), and NONO/p54NRB (Hwang et al, 2009) have been observed in other studies.…”
Section: Discussionmentioning
confidence: 81%